INFLUENCE OF SILICON SUPPLEMENTATION ON THE GROWTH, PHYSIO-CHEMICAL STATUS OF CUCUMBER UNDER SALINE CONDITIONS (Journal of Medical & Health Sciences Review, 2025)
Biofortification significantly increased the nutritional quality of many plants and vegetables. Cucumber (Cucumis sativus) is one of the important vegetables of Pakistan, frequently grown in both temperate and tropical climates, making it native to many parts of the globe. To overcome the deficiency of micronutrients, the foliar and soil application of sodium silicates was applied to check whether this application may affect or reduce sodium contents in cucumber. A pot experiment was conducted during the spring of 2023 at the University of Lahore field area. To study the effect of foliar application of sodium silicate on cucumber variety (HYBRID CUCUMBER SAMBA F1) at the concentrations of 0.5 mM, 1.0 mM, 1.5 mM, and 2.0 mM, and salt stress of 60 mM of sodium chloride was conducted. Various growth characteristics such as root and shoot lengths, fresh and dry plant biomass, number of leaves, pigments like chl a, chl b, total carotenoids, relative water content, and inorganic ions were calculated. Some biochemical attributes also studied like total soluble protein, superoxide dismutase (SODs) and peroxidase (POD) activity. It was found that sodium contents increased in cucumber plants by increasing the concentration of sodium silicate under the salt stress via soil application.